2013
DOI: 10.1093/pch/18.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary dysplasia – trends over three decades

Abstract: Mortality from BPD has improved over the past three decades despite significant trends toward more pronounced prematurity and lower birth weights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 27 publications
4
61
0
Order By: Relevance
“…The demographic characteristics and frequency of respiratory interventions and BPD in our cohort are similar to other cohorts from this era. 24,25 Infants admitted to the neonatal intensive care unit (NICU) often require respiratory support 26 and the risk for BPD and long-term adverse effects on pulmonary function is generally higher the earlier the infant is born. 11 …”
Section: Discussionmentioning
confidence: 99%
“…The demographic characteristics and frequency of respiratory interventions and BPD in our cohort are similar to other cohorts from this era. 24,25 Infants admitted to the neonatal intensive care unit (NICU) often require respiratory support 26 and the risk for BPD and long-term adverse effects on pulmonary function is generally higher the earlier the infant is born. 11 …”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by arrest in lung development with severe impairment of alveolar septation and vascular development, leading to the development of pulmonary hypertension. It is well known that male premature neonates are more susceptible than females for the development of many prematurity related morbidities including BPD (Binet et al, 2012; Costeloe et al, 2000; Kraybill et al, 1989; O'Shea et al, 2012; Trembath and Laughon, 2012; Zysman-Colman et al, 2013), however, the underlying molecular mechanism(s) are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, male sex is associated with a greater risk of neonatal mortality and respiratory illness including BPD (5)(6)(7). Previous studies have indicated that this "male disadvantage" following preterm birth is a result of delayed lung maturation (8), but the basis for the delayed maturation is not completely understood.…”
mentioning
confidence: 99%